INTERNALISASI KARAKTER KEMANDIRIAN MELALUI PEMBELAJARAN KONSTRUKTIF DI PERGURUAN TINGGI - Rianawati, Rianawati (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIN Pontianak, 2014)
Students are young generation, the nation’s hope to build a better country. As a young genera-tion, students must have a strong character, independent, responsible, critical, logical, creative, and innovative. Through constructive learning, students are expected to be able to inde-pendently improve and use the knowledge to assess and analyze, solve problems, think active-ly, critically and logically, and take the meaning of what is learned. Therefore, the learning process is student -oriented activities. Constructive learning is not only concerned with the cognitive aspects, but also oriented to the development of skills and noble character of the student. Lecturer facilitates a democratic learning that allows students to develop independent learning. Lecturer served as a facilitator, mentor and director, and evaluator of learning.